The Influence of the Problem Based Learning Model Assisted by the Wordwall Educational Game on Motivation and Learning Outcomes for Class V Social Sciences - Sarmiati Sarmiati; Hidayah Quraisy; Muhammad Nawir (Edumaspul: Jurnal Pendidikan, 2024)
The aim of the research is to determine the influence of the Problem Based Learning model assisted by the Wordwall Educational Game on motivation and social studies learning outcomes for class V. The research design used is Nonequivalent Control Group Design with random techniques. The data analysis technique in this research uses descriptive and inferential statistical analysis. As a requirement, a requirements test is carried out, namely the normality test and homogeneity test. After that, a hypothesis test was carried out using the Manova test. The results of the first hypothesis research using the Paired Samples Test show that the significant value is 0.00<0.05, so it can be concluded that there is an influence of the Problem Based Learning model assisted by the Wordwall Educational Game simultaneously on learning motivation; Test the second hypothesis with a significance value of 0.002<0.05, which means that there is an influence of the Problem Based Learning learning model assisted by the Wordwall Educational Game on social studies learning outcomes for class V students; test the third hypothesis using Multivariate Tests with a significance value of 0.000 < 0.05, which means that there is an influence between the Problem Based Learning learning model assisted by the Wordwall Educational Game on student motivation and learning outcomesThe aim of the research is to determine the influence of the Problem Based Learning model assisted by the Wordwall Educational Game on motivation and social studies learning outcomes for class V. The research design used is Nonequivalent Control Group Design with random techniques. The data analysis technique in this research uses descriptive and inferential statistical analysis. As a requirement, a requirements test is carried out, namely the normality test and homogeneity test. After that, a hypothesis test was carried out using the Manova test. The results of the first hypothesis research using the Paired Samples Test show that the significant value is 0.00<0.05, so it can be concluded that there is an influence of the Problem Based Learning model assisted by the Wordwall Educational Game simultaneously on learning motivation; Test the second hypothesis with a significance value of 0.002<0.05, which means that there is an influence of the Problem Based Learning learning model assisted by the Wordwall Educational Game on social studies learning outcomes for class V students; test the third hypothesis using Multivariate Tests with a significance value of 0.000 < 0.05, which means that there is an influence between the Problem Based Learning learning model assisted by the Wordwall Educational Game on student motivation and learning outcomes